Beyond Artificial Intelligence:The Disappearing Human-Machine Divide - Romportl, Jan (Springer, 2015)
This book is an edited collection of chapters based on the papers presented at the conference “Beyond AI: Artificial Dreams” held in Pilsen in November 2012. The aim of the conference was to question deep-rooted ideas of artificial intelligence and cast critical reflection on methods standing at its foundations.